2015
DOI: 10.1007/s11013-015-9466-3
|View full text |Cite
|
Sign up to set email alerts
|

An Illness of Power: Gender and the Social Causes of Depression

Abstract: There is considerable discourse surrounding the disproportionate diagnosis of women with depression as compared to men, often times cited at a rate around 2:1. While this disparity clearly draws attention to gender, a focus on gender tends to fall away in the study and treatment of depression in neuroscience and psychiatry, which largely understand its workings in mechanistic terms of brain chemistry and neurological processes. I first consider how this brain-centered biological model for depression came about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
(25 reference statements)
3
38
0
3
Order By: Relevance
“…In the present study, we found that being male (T=2.970, p=0.004, 95%CI: 2.667~13.521) was a protective factor for depression in doctors. There is considerable discourse surrounding the disproportionate diagnosis of men with depression as compared to women, often times cited at a rate around 1:2 (23). However, the view that depression rates are universally higher in women is challenged, as biological determinants, sex role changes, and social factors might also contribute to this difference (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that being male (T=2.970, p=0.004, 95%CI: 2.667~13.521) was a protective factor for depression in doctors. There is considerable discourse surrounding the disproportionate diagnosis of men with depression as compared to women, often times cited at a rate around 1:2 (23). However, the view that depression rates are universally higher in women is challenged, as biological determinants, sex role changes, and social factors might also contribute to this difference (24).…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, given sex differences in the prevalence of depression, female nurses are particularly vulnerable to perceive the symptoms of depression. 6 Therefore, this study was conducted only in female nurses. There are a great deal of studies indicating that negative mental states such as depressive symptoms had a detrimental impact on the quality of care provided by nurses, and hence, affected patient's medical treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Each questionnaire, in their material‐semiotic composition, may develop from broader cultural anxieties about increasing social complexity, economic uncertainty, or environmental interferences. Indeed, several critical cultural analyses have shown depression to be entwined with agency and structural conditions (Ingersoll, ; Neitzke, ). It might also be noted that whether the current DSM‐5 is a factor in a specific questionnaire choice remains unclear.…”
Section: The Rhetorical Pinch Of Psychometric Questionnairesmentioning
confidence: 99%